In vitro activity of dactimicin, a novel pseudodisaccharide aminoglycoside, compared with activities of other aminoglycosides. - Gu, J W (1989)
The in vitro activity of dactimicin, a new pseudodisaccharide aminoglycoside which possesses a formimidoyl group, was compared with those of gentamicin, tobramycin, and amikacin against 500 isolates. Dactimicin inhibited 90% of isolates from the family Enterobacteriaceae at a concentration of less than or equal to 4 micrograms/ml. It was more active than amikacin against Klebsiella pneumoniae, Serratia marcescens, Citrobacter diversus, Enterobacter agglomerans, Yersinia species, and Salmonella species, with an MIC for 90% of the strains (MIC90) of less than or equal to 4 micrograms/ml. The MIC90s for the Pseudomonas aeruginosa isolates were greater than 128 micrograms/ml. Dactimicin did not inhibit most methicillin-resistant Staphylococcus aureus isolates and coagulase-negative staphylococci but had an MIC50 (MIC for 50% of strains tested) of 2 micrograms/ml against methicillin-susceptible S. aureus isolates and coagulase-negative staphylococci. Dactimicin in combination with piperacillin acted synergistically against 75% of Escherichia coli, K. pneumoniae, S. marcescens, and S. aureus isolates. It exhibited an excellent postantibiotic suppressive effect on E. coli. Dactimicin was active against organisms possessing aminoglycoside-modifying enzymes including AAC(2')-b, AAC(3)-III, -IV, and -V, and AAC(6')-Ia, -Ib, Ic, -II, and -IV but was not active against isolates which contained AAC(3)-I and the bifunctional APH(2")-AAC(6')-I. Its lack of activity against P. aeruginosa appeared to be permeability related since in the presence of EDTA P. aeruginosa was susceptible, as were mutant isolates resistant because of permeability barriers.